Letter from Guthrie and Haldeman to James Curtis Booth, November 19, 1856 - Guthrie, W. W.; Haldeman, T. J. G. (1856)
Requisition of alloyed metals from the local inspectors of Cincinnati, Ohio.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Alloys